Diseño e implementación de un enlace de radio para interconectar la oficina matriz de la Cooperativa Puéllaro y sus sucursales - Patiño Tapia, Silvana Isabel (2017)
In general telecommunications, refer to a set of techniques, for sending and receiving information of any nature between two points separated geographically, using different transmission media. Given their importance, telecommunications are today one of the most important strategic sectors for any organization and / or country, because it contributes directly to the economic, social and technological development of its members and its society in general. The main objective of this project is to design and implement a radio link between the headquarters office of the “Cooperativa de Ahorro y Crédito Puéllaro” and its branches located in the sectors of Solanda and Puéllaro to optimize the development of its internal activities and improve the services that Provides the community it serves. During this Project execution, each link was designed analyzing its logical and physical components, the logical part was covered to refer to the hierarchical structure of the solution, the IP addressing and the configuration of the accessories and the other side in relation to the physical design It emphasized the physical inspection of each site (agencies and RBS), in order to know if it is necessary to carry out some type of civil intervention on the buildings. As a result of the project, three radio links were installed and configured for each agency of the Cooperativa Puéllaro and its main office located in Carapungo. Additionally, the respective communication and monitoring tests were carried out from the main office link to the two branches, in order to improve connectivity as well as the internet and data service.